Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1159/000448114
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors in the Treatment of Choroidal Metastases from Non-Small-Cell Lung Cancer: A Case Report and Review of Literature

Abstract: Background: Choroidal metastases being the sole presenting feature of lung cancer is rare. Erlotinib, a tyrosine kinase inhibitor (TKI), is used in the treatment of lung adenocarcinoma where tumor cells exhibit epidermal growth factor receptor (EGFR) mutations. We report a case of metastatic non-small-cell lung cancer (NSCLC) with choroidal metastasis, which was the sole presenting feature and which responded to erlotinib. Methods: We performed a retrospective case review. Case: A 78-year-old man presented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…5 The development of targeted therapy, especially in pulmonary adenocarcinoma patients with EGFR mutations, provides a therapeutic modality using TKI, which in several case reports gave an improved response to pulmonary adenocarcinoma with eye and orbital metastases. 5,6 Pulmonary adenocarcinoma patients with metastases and EGFR mutations who received TKI therapy had a 5-year survival rate of 14.6%. Deletion of exon 19 and absence of extrathoracic and brain metastases provide better survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The development of targeted therapy, especially in pulmonary adenocarcinoma patients with EGFR mutations, provides a therapeutic modality using TKI, which in several case reports gave an improved response to pulmonary adenocarcinoma with eye and orbital metastases. 5,6 Pulmonary adenocarcinoma patients with metastases and EGFR mutations who received TKI therapy had a 5-year survival rate of 14.6%. Deletion of exon 19 and absence of extrathoracic and brain metastases provide better survival.…”
Section: Discussionmentioning
confidence: 99%
“…4 The development of targeted therapy in pulmonary adenocarcinoma with epidermal growth factor receptor (EGFR) mutations provides a therapeutic modality using tyrosine kinase inhibitors (TKI), which in some case reports provide better outcome to pulmonary adenocarcinoma with eye and orbital metastases. 5,6 A 64-year-old male patient complained of swelling, redness, painful and protruded left eye. Initially, the patient experienced a slowly-blurred left eye and narrowed vision of the left eye, resulted in complete loss of vision accompanied by eye pain.…”
Section: Introductionmentioning
confidence: 99%
“…The first described choroidal metastasis cases in possibly EGFR-mutant Asian patients (not molecularly assessed), published in 2009–2010, revealed the efficacy of EGFR TKI (in association with intravitreal bevacizumab) [ 15 , 16 ]. Since then, a few case reports have confirmed the ability of first- or second-generation TKIs to induce choroidal metastasis regression in patients with tumor EGFR mutation [ 7 , 17 , 18 ]. The efficacy of third-generation EGFR TKI osimertinib on choroidal metastasis was reported once in an NSCLC patient with T790M EGFR tumor mutation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our case, both of these patients were initially treated with erlotinib, but eventual disease progression necessitated the switch to osimertinib as second-line treatment. Nair et al [13] reported a case of choroidal metastasis from NSCLC successfully treated with erlotinib. In this review, the authors summarized 8 other cases [14][15][16][17][18][19] of choroidal metastasis from NSCLC treated with first-generation EGFR-TKIs in the literature (erlotinib and gefitinib), finding that the majority of cases improved following treatment with TKIs, thereby suggesting that this class of medication may play an important role in the management of this cohort of patients.…”
Section: Discussionmentioning
confidence: 99%